NUMERICAL OPTIMIZATION OF SANDWICH COMPOSITE STRUCTURE UNDER FLEXURAL LOAD (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
The structures of a sandwich composite have been utilized in the aerospace industry andengineering applications. Prediction of a theoretical composite construction's flexuralproperties is important for efficient composite products design. In this investigation, fourdifferent core shapes were used in the fabrication of the sandwich frames with constantvolume of sandwich composite structure in each case; these are hexagonal, rectangular,triangular and circular. The effect of core stiffeners number was studied to finding the beststiffeners number which gives the highest properties in strength using the finite elementanalysis.The material of the each face sheet is consisting from epoxy with four layers of a wovenfiberglass laminate construction, and the core stiffener material consists from epoxy matrixwith carbon fiber, the fiber volume fraction was 60% for both skins and core composites.The analysis of the three point bending load with a value of (10 kN) conducted byconstructing a finite element model, explained that the best shape of core was rectangularwhich give less deflection value of (11.939 mm) from the other shapes, for the sameproperties of material and constant core volume in each case. Also, it was determined theoptimum stiffeners number, for the rectangular core, was five stiffeners in longitudinaldirection and twelve stiffeners in transverse direction, gives strengthen structure.